Answer (4):
a=ub/k because
u=ak/b (starting equation)
ub=ak (multiply b to both sides)
a=ub/k (divide both sides by k)
Answer (6)
x=g+c-y because
g=x-c+y (starting equation)
x+y=g+c (add c to both sides)
x=g+c-y (subtract y from both sides)
Answer:
the first one is: 351-400
the second one is: 651-700
Step-by-step explanation:
Hope it helped
Answer:
<u>10</u>
Step-by-step explanation:
Formula :
Finding a₅ :
- a₅ = -5 + a₄
- a₅ = -5 + 20
- a₅ = 15
Finding a₆ :
- a₆ = -5 + a₅
- a₆ = -5 + 15
- a₆ = <u>10</u>
MrBillDoesMath!
Answer: The first radio button choice 8/3 * m^8
Steps:
120 (m^ 16) / 45 (m^8) =
120/45 * (m^16)/(m^8) =
Simplify 120/45 (15 or 5 *3 divides each). Since base "m" is same in both terms simply subtract exponents.
8/3 ( m^(16 - 8)) =
8/3 * m^8
MrB
Answer:
9.4
Step-by-step explanation: